Eksplorasi furnitur meja belajar Braille untuk kebutuhan disabilitas tunanetra - Muhammad Fiqih Sabelputra; Andriano Simarmata; Rachmi Kumala Widyasari (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2026)
This design project explores Braille learning furniture, specifically a desk used by visually impaired individuals for reading and writing Braille. The study identifies several challenges faced by the visually impaired, including physiological comfort, ergonomic needs, and psychological aspects related to learning motivation. The design methodology involves observation and exploration. Observations were conducted in the Braille library of the Wyata Guna Foundation and during Braille reading and writing activities. The experimental method included sketching, 3D modeling, and the creation of 1:1 scale prototype to find the optimal design solution for Braille learning desks. Exploration also focused on features that enhance users' physiological and psychological comfort. Among the designs explored, the most effective one (furniture code E2H) was selected. This design includes a 35° table tilt to support forward-leaning posture, the use of cork material for sensory feedback, a table organizer, and motivational quotes in Braille to improve both physiological and psychological comfort during Braille learning. The aim of this study is to develop Braille learning furniture to assist the visually impaired in learning Braille, ultimately enhancing their learning potential and quality of life.